KARAKTERISTIK POLA PEMBELAJARAN ANAK USIA MI, MTS DAN MA DITINJAU DARI SENI MENDIDIK SAYYIDINA ALI BIN ABI THALIB - Nurlisma (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Education in Islam has a very large portion related to the pattern of educating children, because each phase of children's growth has different characteristics and treatments according to their respective ages. To get optimal children's education based on Islamic teachings they need someone who helps the process and its development, there will be many factors that influence it, such as family, school, and community environment. Thus educating children according to their time and according to their age is very important to be considered and followed up, each phase and age requires different handling, therefore parents, teachers and the community play an important role for the success of children's education. Ages 0-7 years, 7 to 14 years, 15 to 21 years there are separate procedures according to age and development, the stages of educating are according to the teachings of the Prophet and Sayyidina Ali Bin Abi Talib, in formal education in madrasas the pattern of applying the art of educating children is also applied in schools. in madrasa education with learning patterns for children aged MI, MTs and MA. The purpose of Islamic education is to perfect, clean, purify and be able to bring the human heart to draw closer to Allah swt, to create a perfect Muslim person who is faithful, pious, knowledgeable, works and has a noble character in carrying out the mandate as a caliph and servant of Allah.